Teorija i metodologija sportivnoj podgotovki: blokovaja sistema trenirovki sportsmenov vysokogo klassa - Verchoshanskij, J. V. (Teorija i Praktika fiziceskoj Kul'tury, 2005)
In the paper theoretical foundations and experimental arguments for the changing traditional paradigm of the theory and methodology of sport training (T&M of ST) for high class athletes are studied. They must be based on its biological composing. The relationships between external and inside relations of an organism as well as their dynamics during the development of the process of long adaptation to the sport activity were analyzed. The idealized object of the T&M of ST - a process of attaining of sport mastery - has been developed and the main regularities of it were formulated. The theory, the main principles of construction of the unconventional block-system of the sport training for annual cycle and technology of its realization were discussed.